(untitled) (The Shivapuri Journal, 2026)
This paper underscores the significance of systems thinking for adaptive military decision-making and problem-solving in complex operational environments. By using an analytical and descriptive approach, this paper reiterates the fact that traditional approaches often fall short to address the interconnected nature of contemporary complex security challenges. Therefore, systems thinking presents holistic tools and frameworks to enhance situational understanding, anticipate second- and third-order effects, and foster organizational agility. It also discusses key principles and practical tools, identifies cognitive biases and institutional barriers, and recommends useful measures to deal with it in the Nepali Army’s context. Furthermore, it concludes that systems thinking emerges as an institutional necessity for enhancing skills for decision-making and problem-solving given the Nepali Army’s formal adoption of IOPP and TPP.